Brain networks associated with anticipatory postural adjustments in Parkinson’s disease patients with freezing of gait - Andrea C. de Lima-Pardini; Daniel B. Coelho; Mariana P. Nucci; Catarina C. Boffino; Alana X. Batista; Raymundo M. de Azevedo Neto; Carla Silva-Batista; Egberto R. Barbosa; Rajal G. Cohen; Fay B. Horak; Luis A. Teixeira; Edson Amaro Jr (NeuroImage: Clinical, 2020)
Specific impairments of anticipatory postural adjustment (APA) during step initiation have been reported in patients with Parkinson’s disease (PD) and freezing of gait (FoG). Although APA disruption has been associated with FoG, there is scarce knowledge about its neural correlates. We sought to better understand the neural networks involved with APA in patients with FoG by assessing the level of hemodynamic response of specific brain regions and the functional connectivity during the leg lifting task. In the current investigation, APAs of patients with PD, with and without (nFoG) freezing were assessed during a leg lifting task in an event-related, functional magnetic resonance imaging (er-fMRI) protocol. Results identified a high hemodynamic response in the right anterior insula (AI) and supplementary motor area (SMA) in the FoG group when an APA was required. The nFoG had stronger connectivity between the right and left insulae than the FoG group. The strength of this connectivity was negatively correlated with the severity of FoG. Both groups showed different brain network organizations comprising the SMA and the bilateral AI. The SMA was found to be a hub in patients with FoG when an APA was required for the task. Our findings suggest that both groups used compensatory mechanism comprising the insulae during APA. Neither group used the entire network comprised of the insulae and SMA to accomplish the task. The FoG group relied more on SMA as a hub than as part of a broader network to exchange information during the APA.